Penerapan Metode Inquiri Untuk Meningkatkan Hasil Belajar Fisika Siswa Pada Materi Besaran Dan Satuan - muntasir muntasir (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2021)
The method was an important factor that needs to be mastered by teachers in carrying out learning in schools. To obtain good student learning outcomes, every teacher should be able to use methods that are in accordance with the material presented. Because not all methods are suitable for every subject matter presented, but there are methods that are more suitable for certain materials and not or less suitable for other materials. One of the efforts that must be done is to find teaching methods that are able to invite students to be more active in learning activities and train students to learn a lot on their own. Based on the background of the problem above, the formulation of the problem in this research is: "Is the application of the inquiry method able to improve student physics learning outcomes on the material of quantities and units in class X SMA Negeri 1 Jeunieb in the 2019/2020 academic year?" The goal to be achieved in this study was to improve student physics learning outcomes through the application of the inquiry method to the material of quantities and units in class X SMA Negeri 1 Jeunieb in the 2019/2020 academic year. This study consisted of two cycles, each cycle consisting of two meetings. The research subjects were students of class X IPA-1 SMA Negeri 1 Jeunieb in the odd semester of the 2019/2020 academic year, totaling 38 students. Through the application of the inquiry method, students can improve their physics learning outcomes on the material of quantities and units in class X SMA Negeri 1 Jeunieb for the 2019/2020 academic year. This can be seen from the results of the evaluation of student learning from the first cycle reaching 68.42% of students completed classically, while in the second cycle it increased to 89.47%.